Study of the Applicability Level of Merge Cube Augmented Reality Media on Junior Hight School Science Teachers - Taufiq, Muhamad; Nuswowati, Murbangun; Widiyatmoko, Arif (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
Science learning media based on Merge Cube Augmented Reality (AR) has been developed. This research aims to determine the level of applicability of science learning media based on Merge Cube AR to users, especially junior high school science teachers. The research method was carried out through a descriptive survey after testing the use of science learning media based on Merge Cube Augmented Reality. The respondents of this research were 41 teachers from 13 different junior hight schools. Based on the analysis data showed that respondents were very confident of being able to apply Merge Cube AR media in science learning and the percentage of applicability level in this description reach 87.8%, those indicate that the media is in very good criteria. Teachers are very confident that they can achieve learning goals by implementing Merge Cube AR learning media. The percentage of applicability level in this description reach 82.9%, those indicate that the media is in very good criteria. The results of the analysis also show that teachers are strongly believe that the Merge Cube AR media helps them in a more effective way to deliver science learning activity. The percentage of applicability level in this description reach 90.3%, those also indicate that the media is in very good criteria. The average percentage of applicability level reach 87.0 %, it is indicated that the applicability level of science learning media based on merge cube ar in the very good criteria. It can be concluded that science learning media based on Merge Cube AR has a very good level of applicability and can be used in science learning.